SOME KEY ISSUES IN RECONSTRUCTIONS OF PROTEROZOIC SUPERCONTINENTS - Zhao G.; Sun M.; Zhang J.; Wilde S.A.; Li S. (My University, 2006)
Supercontinents containing most of the earth's continental crust are considered to have existed at least twice in Proterozoic time. The younger one, Rodinia, formed at ~1.0 Ga by accretion and collision of fragments produced by breakup of the older supercontinent, Columbia, which was assembled by global-scale 2.0-1.8 Ga collisional events. Little consensus has been reached regarding configurations of these supercontinents because of some unresolved issues concerning continental fits. One of these issues concerns how Siberia was related to Laurentia. Previous reconstructions that consider the Aldan Shield of Siberia as a continuation of the Wyoming Province of Laurentia have been largely abandoned in favor of models connecting Siberia to northern Laurentia, but it remains controversial which part of Siberia is contiguous with northern Laurentia. Also at issue is the western Laurentia-Australia-East Antarctica connection. Most Rodinia reconstructions place Australia, together with East Antarctica, adjacent to either western Canada (the SWEAT hypothesis) or the western United States (the AUSWUS hypothesis). However, recent studies combining paleomagnetic and isotopic age data have called into question the validity of SWEAT, AUSWUS and other variants. Another issue is the position of North China in Rodinia/Columbia. Limited paleomagnetic data seem to be consistent with the Paleo-Mesoproterozoic North China-Siberia/Baltica connection, whereas geological data support the recently proposed Archean to Mesoproterozoic North China-India connection. Controversial issues have also been raised about the timing and history of the amalgamation and fragmentation of South America and West Africa. Both geological and paleomagnetic data suggest that South America (São Francisco and Amazonia Cratons) and West Africa (Congo and West African Cratons) coalesced into a single landmass along the 2.1-2.0 Ga Transamazonian/Eburnean orogens. However, whether they were divorced and then re-married to form part of Gondwana, or remained largely coherent from their amalgamation at 2.1-2.0 Ga until their incorporation into Gondwana is unclear. Also little known is the position of Amazonia-West Africa in the proposed supercontinents, with some workers believing that they existed as a separate landmass, whereas others place Amazonia-West Africa adjacent to Baltica. In summary, although geological and paleomagnetic data are supportive of the existence of Proterozoic supercontinents Rodinia and Columbia, they are insufficient to determine their exact geometries. © 2006 Elsevier Ltd. All rights reserved.
Keywords: GEOLOGICAL CORRELATIONS; PALEO-MESOPROTEROZOIC; PALEOMAGNETISM; RECONSTRUCTION; SUPERCONTINENT; Archean; Mesoproterozoic; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская